2019
DOI: 10.3389/fpsyg.2019.00586
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific Low Back Pain and Postural Control During Quiet Standing—A Systematic Review

Abstract: Background: There is a great number of people who require treatment for non-specific low back pain (LBP) yet the causes are still unclear. One proposed cause for LBP is impaired motor control and more specific an impaired postural control. Objective: The purpose of this review is to provide an overview of postural control parameter differences in persons with and without non-specific LBP during quite standing. Methods: A literature search in five datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 41 publications
(199 reference statements)
6
64
0
2
Order By: Relevance
“…Consistent with previous findings, MPCD was more common in the cLBP group (1,2). To determine whether cLBP is related to MPCD generally or to specific features of MPCD, we included tests relevant to MPCD but not cLBP.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with previous findings, MPCD was more common in the cLBP group (1,2). To determine whether cLBP is related to MPCD generally or to specific features of MPCD, we included tests relevant to MPCD but not cLBP.…”
Section: Discussionsupporting
confidence: 63%
“…Motor and postural control deficiencies (MPCD) contribute to chronic, non-specific low back pain (cLBP) [1,2]. However, studies examining training programs to specifically improve MPCD have not shown superiority to general exercise [3], and clinical outcomes are not predictable based on findings of the deep stabilization system [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of standing, recent reviews have confirmed altered motor control in NSLBP [ 9 11 ] based on different parameters. Two of these reviews [ 9 , 10 ] investigate changes in CoP data during different quiet standing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 A recent systematic review by Koch and Hȁnsel (2019) also concluded that there were differences in certain parameters of postural control in quiet standing between patients with NSLBP and healthy subjects. 42 A previous study by Sung et al evaluated the lumbar stability index, relative standstill time, of patients with and without LBP and found that the stability index significantly decreased, particularly when visual feedback was blocked, for patients with LBP. 43 In the present study, patients with subacute NSLBP demonstrated a shorter single-leg standing time than healthy control subjects, even with their eyes open.…”
Section: Discussionmentioning
confidence: 99%